SISTEM RELIGI DAN UPACARA KEAGAMAAN MASYARAKAT BADUY - Resti Hidayat; Sapriya; Encep Supriatna; Putri Fajriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Baduy people, who live in Banten, Indonesia, adhere to a traditional belief called Sunda Wiwitan. Respect for ancestors, the power of nature, and belief in the Blessed One (the Almighty) are the basis of this religious system. The purpose of this article is to study the religious system and religious ceremonies of the Baduy people, as well as the customary values reflected in their religious practices. Data was obtained by conducting literature research with sources from 2020–2024. The study shows that the religious system of the Baduy people serves as a spiritual guide and contributes to social and environmental balance.